Angiogenesis in Patients with Chronic Heart Failure: Focus on Endothelial Vascular Growth Factor, Pentraxin-3 and Transforming Growth Factor Beta - R. N. Shepel; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Chronic heart failure (CHF) is considered the leading cause of death in patients with established cardiovascular (CVD) and metabolic diseases. Although the current treatment strategy has improved survival and clinical outcomes, the prevalence of CHF shows an increase. Current clinical guidelines for the treatment and prevention of CVD note the role of biological markers as a fairly simple and powerful tool for diagnosing, stratifying risk and predicting CHF. However, it is unclear whether all of these biological markers are equally capable of predicting cardiovascular mortality and heart failure related outcomes in patients with acute and chronic heart failure, as well as in different phenotypes of heart failure. However, the results of numerous studies demonstrate scientific interest in the processes of angiogenesis among patients with CHF. There is an impressive body of evidence linking CHF to the level of markers such as vascular endothelial growth factor, pentraxin-3, and transforming growth factor beta. The review presents the data of domestic and foreign clinical studies devoted to the study of the level of angiogenesis markers among patients with CHF.